New testament studies (Cambridge University Press)
New Testament Studies is an international peer-reviewed periodical whose contributors include the leading New Testament scholars writing in the world today. The journal publishes original articles and short studies in English, French and German on a wide range of issues pertaining to the origins, history, context and theology of the New Testament and early Christianity
Keywords: Religion